Komunikasi Qur’ani dalam Sistem Pengasuhan di Pondok Pesantren Darul Huda Wonodadi - Muttaqin, Asyharul; Nisa', Zulia Khoirun (Universitas Nahdlatul Ulama Blitar, 2024)
This research explores how Islamic boarding schools apply communication in accordance with the teachings of the Koran to shape the Islamic character of the students. The character building process is carried out through various activities participated in by students. However, in their learning and development process, problems such as violence between students and bullying often arise. Therefore, a serious approach is needed in dealing with problems that occur in the student learning process. The research uses Qur'anic communication and parenting theory. The research method used is qualitative descriptive analytical, by conducting research at the Darul Huda Islamic Boarding School and analyzing the findings using Qur'anic communication theory. The findings in this research state that the parenting system applies Qur'anic communication. The parenting here is based on the principles of Qoulan Ma'rufa, Qoulan Sadida, Qoulan Baligha, Qoulan Karima, Qoulan Maisura, Qaulan Layyina, Qaulan Tsaqila, Qoulan 'Azhima, and Ahsanu Qaulan. Implementing Qur'anic communication can also handle bullying cases. Darul Huda Islamic Boarding School uses a persuasive, wise, humanist, polite and intuitive model. Apart from that, the implementation of communication based on the Koran has a comprehensive and effective approach, method and model, which can be used by caregivers in preventing and dealing with violence and bullying that occurs among students.